Using testosterone and cortisol as biomarker for training individualization in elite basketball - Schelling, X.; Calleja-Gonzalez, J.; Torres-Ronda, L.; Terrados, N. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to determine the responses of testosterone and cortisol, with special reference to playing positions, playing time (PT), and phase of the season. We performed a follow-up study during 4 consecutive seasons to investigate the effects of PT, positional role, and phase of the season on anabolic-catabolic biomarkers (plasma total testosterone -TT- and cortisol -C-) on 20 professional male basketball players (27.0 ± 4.2 years; 24.4 ± 1.2 kg/m). First blood samples were collected right after the off-season period and considered as baseline. Samples were taken periodically every 4-6 weeks, always after a 24- to 36-hour break after the last game played. Statistical procedures were nonparametric mainly. Hormonal status was playing position-dependent, power forward (PF) showed the lowest TT values (median ± interquartile range [IQR]; PF: 18.1 ± 4.9; nmol/L), and small forwards showed the highest ones of cortisol (0.55 ± 0.118 µmol/L). Players who played between 13 and 25 minutes per game showed the highest values of TT (22.8 ± 6.9 nmol/L) and TT/C (47.1 ± 21.2). March and April showed the most catabolic or stressed hormonal state (low TT/C values and high ones of cortisol) and that is necessary to take into account according to PT (>25-minute per game) and specific playing position. Monitoring plasma TT and cortisol is recommended to prevent excessive stress caused by professional basketball season requirements.